2014
DOI: 10.5648/jjiao.32.13
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the desmosomal cadherin desmoglein-2 suppresses colon cancer cell proliferation through EGFR signaling

Abstract: Desmosomal cadherins mediate cell-cell adhesion in epithelial tissues and have been known to be altered in cancer. We have previously shown that one of the two intestinal epithelial desmosomal cadherins, desmocollin-2 (Dsc2) loss promotes colonic epithelial carcinoma cell proliferation and tumor formation. In this study we show that loss of the other intestinal desmosomal cadherin, desmoglein-2 (Dsg2) that pairs with Dsc2, results in decreased epithelial cell proliferation and suppressed xenograft tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Previous studies have demonstrated that desmosomes are affected by calcium influx into the cell (28) and that homophilic and heterophilic interactions between DSC and DSG proteins generate cell aggregation (29,30). It has also been shown that desmosomal protein expression may be altered during cancer development (31,32) and may regulate cell proliferation (33). We found that DSG2 is expressed in HCT116 cells (Fig.…”
Section: Desmosomal Proteins Also Coordinate Cell Aggregationsupporting
confidence: 52%
“…Previous studies have demonstrated that desmosomes are affected by calcium influx into the cell (28) and that homophilic and heterophilic interactions between DSC and DSG proteins generate cell aggregation (29,30). It has also been shown that desmosomal protein expression may be altered during cancer development (31,32) and may regulate cell proliferation (33). We found that DSG2 is expressed in HCT116 cells (Fig.…”
Section: Desmosomal Proteins Also Coordinate Cell Aggregationsupporting
confidence: 52%
“…Reduced expression of desmosomal cadherins, which may be responsible for the weakening of cell-cell adhesion observed in cancer cells, was observed in different tumors, such as skin, 151 head and neck, 152 lung, 153 breast, 154 and a variety of other epithelial malignancies, 155 including gastric 156 and colon 157 cancers. In one example, knockdown of Pkp3 in colon cancer cells promoted anchorage-independent growth and tumor growth in immunocompromised mice.…”
Section: The Desmosome In Cancermentioning
confidence: 99%